2017
DOI: 10.1111/epi.13938
|View full text |Cite
|
Sign up to set email alerts
|

Indications and methodology for video‐electroencephalographic studies in the epilepsy monitoring unit

Abstract: SummaryAlthough the epilepsy and neurology communities have position papers on a number of topics pertaining to epilepsy diagnosis and management, no current paper exists for the rationale and appropriate indications for epilepsy monitoring unit (EMU) evaluation. General neurologists, hospital administrators, and insurers also have yet to fully understand the role this type of testing has in the diagnosis and management of individuals with paroxysmal neurologic symptoms. This review outlines the indications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 86 publications
1
44
0
1
Order By: Relevance
“…Moreover, AVEM may be of added benefit to patients who report seizures or events resembling epilepsy that occur in certain environments or with specific triggers that may not be replicated in the hospital setting [27]. Hospital setting may be medically necessary for diagnostic evaluation of events when acute medical intervention is potentially needed (e.g., prolonged seizures), when additional seizure testing is required (such as ictal SPECT, semiology assessment that cannot be reliably performed at home), or when diagnostic plan-of-care includes physician-guided antiepileptic medication reduction in an attempt to bring on a seizure during VEM [28]. Inpatient VEM should remain the accepted gold-standard diagnostic test for evaluating events and should be the mainstay of evaluation at academic epilepsy centers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AVEM may be of added benefit to patients who report seizures or events resembling epilepsy that occur in certain environments or with specific triggers that may not be replicated in the hospital setting [27]. Hospital setting may be medically necessary for diagnostic evaluation of events when acute medical intervention is potentially needed (e.g., prolonged seizures), when additional seizure testing is required (such as ictal SPECT, semiology assessment that cannot be reliably performed at home), or when diagnostic plan-of-care includes physician-guided antiepileptic medication reduction in an attempt to bring on a seizure during VEM [28]. Inpatient VEM should remain the accepted gold-standard diagnostic test for evaluating events and should be the mainstay of evaluation at academic epilepsy centers.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for the diagnosis of epilepsy remains prolonged EEG-video monitoring in an inpatient EMU. 1,13,14 There are advantages and disadvantages for the prolonged video monitoring to be done in each setting 3,4,15 ; however, with rising technological advancement in ambulatory video quality as well as accessibility to patients, the ambulatory method has become more prevalent in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…It is safe to say that long-term video-EEG monitoring is the gold standard to confirm the diagnosis, classification and localization of epileptic seizures. 9 A study by X. Liu et al 10 concluded that the first-hour sleep EEG is able to reliably predict the occurrence of IEDs during long-term video-EEG recording and can be utilized as a time-efficient method to identify patients with IEDs, mitigating the burden in the adult epilepsy monitoring unit. Guidelines suggest that antiepileptic drugs (AEDs) are indicated as the first treatment option and shall follow those of other epilepsies.…”
Section: Discussionmentioning
confidence: 99%